Study Evaluasi Pemasangan Pembangkit Listrik Tenaga Surya Sistem Hybrid pada PT. Makmur Indah Selaras Internasional Kabupaten Muaro Jambi Provinsi Jambi - Saputra, Hendi; Thamrin, NJ.; Yusiana, Venny (Journal of Electrical Power Control and Automation (JEPCA), 2024)
PT. Makmur Indah Selaras is an oil palm industry company operating in Muaro Jambi Regency, Jambi Province. For the industrial sector, electrical energy is needed for lighting as well as electric machines and motors. At PT. Makmur Indah Selaras Internasional this has led to an increase in the need for electrical energy. Solutions for the development of electrical energy needs at PT. Makmur Indah Selaras Internasional is by replacing the roof with solar panels with the use of new renewable energy (NRE) New renewable energy which is provided in the form of solar power plants. Roof to maximize the use of solar roofs as land in the application of solar panels. Calculating the power produced by PLTS HYBRID PT. Makmur Indah Selaras International. Calculating the number of materials and components used in PLTS HYBRID PT. prosperous Indah Selaras International. Electrical energy is produced during the day more than in the morning or evening. The average energy produced during the day is 379 -389 Volts.